COVID-19 Pandemic in the italian digital media: media behavior and citizen information consumption during the health crisis. - Sánchez,Javier Sierra (2021)
Abstract his article studies media behavior and information consumption during the COVID-19 health crisis using quantitative content analysis of the news published by Italian digital media between January 1 and April 27, 2020 (n = 841,786). The data shows a direct relationship between the number of publications and the capacity for engagement and a greater reach with classic general media and with Facebook.